The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/asia.202100873
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Activity of Atrane‐type Hard and Soft Lewis Superacids with a Silyl, Germyl, or Stannyl Cationic Center

Abstract: The synthesis and isolation of atrane‐type molecules 1E+ (E=Si, Ge, or Sn) having a cationic group 14 elemental center are reported. The cations 1E+ act as hard and soft Lewis superacids, which readily interact with various hard and soft Lewis basic substrates. The rigid atrane framework stabilizes the localized positive charge on the elemental center and assists the formation of the well‐defined highly coordinated states of 1E+. The cations were applied to the hydrodefluorination, Friedel‐Crafts reaction, alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The yield did not rise as the temperature increased beyond 100 °C (Table 1, entry 15). In addition, the effect of the reaction time using 6 mol% catalyst 1 and 100 °C temperature was studied (Table 1, entries [16][17][18]. The reaction was also performed at ambient temperature under solvent-free conditions, and the resulting yield of the product was low (Table 1, entry 19).…”
Section: Synthesis Of 5-substituted 1h-tetrazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield did not rise as the temperature increased beyond 100 °C (Table 1, entry 15). In addition, the effect of the reaction time using 6 mol% catalyst 1 and 100 °C temperature was studied (Table 1, entries [16][17][18]. The reaction was also performed at ambient temperature under solvent-free conditions, and the resulting yield of the product was low (Table 1, entry 19).…”
Section: Synthesis Of 5-substituted 1h-tetrazolesmentioning
confidence: 99%
“…[11][12][13][14][15][16] In recent years, group 14 elements have been used to design and develop a variety of Lewis acid catalysts. [17][18][19] However, tetravalent germanium(IV) catalysts have been scarcely reported in the literature. Initially, Ge(IV) compounds had been chosen as catalysts for polymerization of ε-caprolactone.…”
Section: Introductionmentioning
confidence: 99%
“…Among a lot of such species, [9][10][11][12][13] the research group of Kawashima demonstrated that 1-hydro-5-carbaphosphatrane and 1-hydro-6-carbaphosphatrane could form an "anti-apicophilic" arrangement. [14][15][16][17] Thus, the skeletons of I and II could supply the diverse electronic structures and have unique functionalities, such as superbase, [18][19][20] catalysis [21][22][23] and biological activity. [24][25][26][27] Alder and coworkers synthesized various derivatives of I and II and related species.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] A number of Lewis acid catalysts of group 14 elements have been developed. [17][18][19] However, the Lewis acid catalyst of germanium (IV) is limited in the literature. Recently, substituted catecholate ligands have successfully been employed in the synthesis of germanium(IV) compounds.…”
Section: Introductionmentioning
confidence: 99%